2006
DOI: 10.1080/10715760600824902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyphenolic extract, Pycnogenol®, on the level of 8-oxoguanine in children suffering from attention deficit/hyperactivity disorder

Abstract: The purpose of this randomized, double-blind and placebo controlled study was to test the effect of polyphenolic extract of pine bark Pycnogenol (Pyc) on the level of oxidized purines represented by 8-oxo-7,8-dihydroguanine (8-oxoG) and on the total antioxidant status (TAS) in children with attention deficit/hyperactivity disorder (ADHD).We have found significantly increased damage to DNA in ADHD children when compared to controls. 8-oxoG was significantly lower after 1 month of Pyc administration in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 23 publications
2
80
0
Order By: Relevance
“…Impaired oxidative status has also been reported for ADHD, and a randomized, controlled trial of Pycnogenol, a pine bark extract with potent antioxidant properties, in children diagnosed with ADHD (n=61) has found symptomatic and biochemical improvements (Chovanova et al, 2006;Dvorakova et al, 2006;Trebaticka et al, 2006). On the other hand, a small (n=24) study comparing Pycnogenol and methylphenidate in adult ADHD has failed to show any advantage of either treatment over placebo (Tenenbaum et al, 2002).…”
Section: Other Conditionsmentioning
confidence: 99%
“…Impaired oxidative status has also been reported for ADHD, and a randomized, controlled trial of Pycnogenol, a pine bark extract with potent antioxidant properties, in children diagnosed with ADHD (n=61) has found symptomatic and biochemical improvements (Chovanova et al, 2006;Dvorakova et al, 2006;Trebaticka et al, 2006). On the other hand, a small (n=24) study comparing Pycnogenol and methylphenidate in adult ADHD has failed to show any advantage of either treatment over placebo (Tenenbaum et al, 2002).…”
Section: Other Conditionsmentioning
confidence: 99%
“…A protective effect of PYC has also been demonstrated on lymphocyte DNA, in an in vitro study (Vagá&ová, personal communication) and in a clinical study (Chovanová et al, 2006). The beneficial chemoprotective effect of EGb 761 against radiationinduced clastogenic factors (Emerit et al, 1995), azoxymethane-induced colonic aberrant crypt foci in rats (Suzuki et al, 2004), as well as against forestomach neoplasia in mice induced by benzo(a)pyrene (Agha et al, 2001) has been demonstrated.…”
Section: Introductionmentioning
confidence: 84%
“…Administration of Pycnogenol Ò for the duration of 1 month has been found to normalize TAS in children with ADHD, at the same time improving the redox state by significantly decreasing oxidized glutathione levels and increasing GSH levels (Dvorakova et al, 2006). In comparison with healthy children, children with ADHD have increased DNA (Chovanova et al, 2006). Pycnogenol Ò administration for 1 month resulted in a significant reduction of hyperactivity, an improvement in attention, concentration, and visual-motoric coordination (Chovanova et al, 2006).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 98%
“…In comparison with healthy children, children with ADHD have increased DNA (Chovanova et al, 2006). Pycnogenol Ò administration for 1 month resulted in a significant reduction of hyperactivity, an improvement in attention, concentration, and visual-motoric coordination (Chovanova et al, 2006).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 98%